Economic reforms: Policy and institutions some lessons from Indian reforms - Arvind Virmani (Indian Council for Research on International Economic Relations (ICRIER), 2004)
Economic policy and policy reform over the last few decades has been motivated by the need to accelerate growth or equivalently to reverse a decline in growth rate. The economic literature on the determinants of growth has burgeoned and disagreement has followed consensus on the policy prescriptions that need to befollowed to achieve this purpose. Sometimes the disagreement is exaggerated by the titans of the profession, so as to distinguish themselves from those constituting the conventional wisdom. The present paper moves the focus from this "macro"debate to concrete issues of policy formulation and policy change and explores the links between policy and institutions in the context of economic reforms. Thus successful introduction of new policies may require new institutions and the degree of success in changing policies may depend on the degree to which existing institutions are modified. The literature on Institutions and Development has dealt with questions of grand design such as the Constitution, the rule of law (personal safety), property rights and informal rules embodied in culture. These are matters that happen on a timescale of a quarter/half century or more and can be thought of as the "superstructure" of institutions. The quantitative work on institutions and growth has explored the linkage between these institutional issues and economic growth. In the current paper we focus on what may be called the "microstructure" of institutions, a smaller scale at which change can occur over a time frame of decades (or half decades). Among the issues that a rise in this context are how changing institutions requirechanges in policies.
Keywords: O1; P41; 330; Economic Reforms; India; Policy; Institutions; Wirtschaftspolitik; Wirtschaftsreform; Politischer Wandel; Institutioneller Wandel; Entwicklung; Indien